PERILAKU HIDUP SEHAT TENTANG PENCEGAHAN PENYAKIT KECACINGAN DI SDN 03 OLAK KEMANG KOTA JAMBI - Fithriyani Fithriyani; Rino M (Jurnal Abdimas Kesehatan (JAK), 2019)
Worm disease is very influential on the health, nutrition and productivity of sufferers. Many diseases are health problems in Indonesia, one of which is worms that are transmitted through the soil. The prevalence of intestinal worms in Indonesia is generally still very high, especially in the disadvantaged population with poor sanitation. the highest incidence of intestinal worms in the Olak Kemang health center was 139 patients and in 2016 100 patients, but despite a decline but at the Olak Kemang Public Health Center the highest incidence of worms. While the number of occurrences occurs a lot at the age of 5-9 years, namely 47 patients where the age stage is the age stage of school children. Target The output of this activity identifies the healthy hygienic behavior of children in SDN 03 Olak Kemang with the method of conducting Health Counseling Clean Healthy Lifestyle about helminthiasis. This activity has a positive impact on students to pay more attention to their health in healthy living behaviors for the prevention of helminthiasis in everyday life. Followed by the role of the Olak Kemang Community Health Center to supervise clean living behavior in children in its working area.